Effect of Planting Density and Harvest Interval on the Leaf Yield and Quality of Moringa (Moringa oleifera) under Diverse Agroecological Conditions of Northern South Africa - M. P. Mabapa; K. K. Ayisi; I. K. Mariga (International Journal of Agronomy)
Smallholder livestock farmers who depend on natural communal grazing lands are particularly vulnerable to climate change as well as to food insecurity and should be encouraged to grow drought-tolerant fodder crops. Moringa oleifera is a highly valued plant, due to its exceptionally high nutritional content. This study was conducted at two experimental sites in the Limpopo province of northern South Africa to evaluate for the first time the effect of plant density and cutting interval on biomass production and chemical composition of moringa grown under two diverse climatic conditions. Four different planting densities (435,000, 300,000, 200,000, and 100,000 plants/ha) were arranged in a randomized complete block design and experimental samples were replicated four times. Data for biomass and gravimetric soil moisture content were collected each time the plants reached a height of 50 cm. Harvested leaves were analysed for chemical composition. An increase in the plant density led to elevated biomass production at both study locations, ranging between 527 and 2867 kg/ha. Moringa is capable of meeting all nutrient requirements of livestock depending on harvest time and location.